PELATIHAN SUMBER PEMBIAYAAN USAHA DALAM PENGEMBANGAN USAHA PADA UKM - Rasyid, Rosmita; Rahadani, Fansisca Puspita; Anggela, Nicole (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
Collecting funding sources has always been a challenge for entrepreneurs. Nowadays, entrepreneurs feel that it's increasingly difficult to obtain the necessary capital to start and expand their businesses. Small and Medium Enterprises (UKM) often face various issues when searching for new funding sources. Various financing patterns for UKM have been devised to address the funding gap problem, especially the capital constraints that can hinder their innovative activities. The selected partner for the Community Service Program (PKM) is a handmade craft business called "Damar Handy Craft," which produces various handmade crafts, such as decorative lamps, seashell handicrafts, and other decorations. Most of the raw materials come from the sea and are processed into these handmade products. The business is located in Serang city, Banten province. The objective of PKM is to assist the partner in enhancing their knowledge and skills in finding and utilizing the right sources of funding for business development. The method used in this program is training and socialization conducted via Zoom. The training on understanding business capital financing covers topics such as basic capital understanding, various sources of funding, the division of passive and active capital, wealth and financial structures, and different forms of capital. The results of the program demonstrate that the partner has acquired knowledge about funding sources that can increase their business capital for business development. The outcomes of the PKM activity include national publication/seminar and writing in intelligent mass media.